Credit Based Scheduling Algorithm in Cloud Computing Environment - Thomas, Antony; Krishnalal, G.; Jagathy Raj, V.P. (Procedia computer science, 2015)
Cloud computing in today's world has become synonymous with good service policies. In order to achieve good services from a cloud, the need for a number of resources arose. But cloud providers are limited by the amount of resources they have, and are thus compelled to strive to maximum utilization. Min-Min algorithm is used to reduce the make span of tasks by considering the task length. Keeping this in mind, cloud providers should achieve user satisfaction. Thus research favors scheduling algorithms that consider both user satisfaction and resources availability. In this paper an improved scheduling algorithm is introduced after analyzing the traditional algorithms which are based on user priority and task length. High prioritized tasks are not given any special importance when they arrive. The proposed approach considers all of these factors. The experimental results show a considerable improvement in the utilization of resources.